2023
DOI: 10.1186/s12903-023-03078-9
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the use of social media on patients changing dental practice: a web-based questionnaire study

Abstract: Background Recent years have seen an increase in the use of social media, by the healthcare sector, including dentistry. Indeed, social media may now be important communication tools for dental practices and patients. This work analyzes the influence of patient (male and female) use of dental practice social media on their decision to change practice. The results also provide insight into the factors patients considered important when choosing a dental practice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 29 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…The present study found a lower percentage 26(17.4%) influenced by information obtained from social media. This was in contrast to a study by Freire et al [9] where a higher percentage 433(86.4%) reported on decision changes. This variance could be attributed to factors such as content credibility, individual preferences, or the nature of dental issues discussed.…”
Section: Impact On Treatment Decisionscontrasting
confidence: 87%
“…The present study found a lower percentage 26(17.4%) influenced by information obtained from social media. This was in contrast to a study by Freire et al [9] where a higher percentage 433(86.4%) reported on decision changes. This variance could be attributed to factors such as content credibility, individual preferences, or the nature of dental issues discussed.…”
Section: Impact On Treatment Decisionscontrasting
confidence: 87%
“…Most of the participants, 283 (62.7%), were males, in contrast to studies conducted by Freire et al [ 22 ] and Al-Ansari et al [ 23 ], where most of them were females, 312 (62%) and 712 (75.4%), respectively. More than half of the participants, 276 (61.2%), were unmarried, belonging to urban areas, 600 (66.5%), and unemployed, 193 (42.8%), which could be attributed to the fact that this sector of the population has greater spare time and ease of access to the Internet to be able to surf across social media platforms much more frequently.…”
Section: Discussionmentioning
confidence: 56%
“…The majority of the participants, 267 (59.2%), spent more than 30 minutes to three hours per day on social media, with Facebook being the most used social media platform (n = 385) followed by YouTube (n = 263) and the least used being Twitter (n = 76). Freire et al [ 22 ] in his study stated that Instagram was the most followed platform (n = 23), followed by Facebook (n = 15), while the least used were YouTube (n = 2) and Twitter (n = 4). According to reports by Global Stats on social media Stats in India as of December 2023, Facebook has been the most popular platform (78.07%), and its wide audience and reach, high engagement rate, improved analytics, accurate targeting, and affordable advertising rates are considered to be its reasons [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…One of the hospital's efforts to build customer loyalty is to build a strong brand image, which will bring brand loyalty to customers (Sacre et al, 2023). Customer loyalty to a brand requires hospitals always to pay attention to their brand image because a strong brand image is an asset https://doi.org/10.12928/commicast.v4i2.8592 owned to get the top position in the minds of consumers/customers (Freire et al, 2023). If the brand image has been accepted by consumers/customers, it will make it easier for hospitals to win market share.…”
mentioning
confidence: 99%